2021
DOI: 10.3390/agronomy11102079
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Effects of Tectona grandis Biochar from Wood Residues on the Growth of Young Cedrela odorata Plants in a Nursery

Abstract: Biochar from agroforestry biomass residues is an alternative source of fertilizers for improving the soil fertility. In Costa Rica, Cedrela odorata is planted in pure plantations and agroforestry systems and different types of substrates are used in the nursery to enhance the growth and performance of the young saplings. The main objective of the present study was to evaluate the growth (in height, diameter, biomass) and distribution of carbon (C), hydrogen (H), and nitrogen (N) for C. odorata plants in a nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some studies evaluated the charcoal and biochar qualities of some Costa Rican tropical woods, including energy densities, energy yields, biochar characteristics, and thermal profiles, in addition to other properties [20,[24][25][26], but when specifically studying the Costa Rican species in slow pyrolysis, Tectona grandis and Gmelina arborea lacked the same attention [27]; however, it does not refer to the effects of temperature in slow pyrolysis [28][29][30][31]. A study carried out on T. grandis by Parthasarathy and Sheeba [32] studied the yield, solid residence time, and charcoal characteristics produced at different temperatures of slow pyrolysis (300 • C, 350 • C, 450 • C, 500 • C, and 550 • C) and demonstrated that the yield of charcoal decreased, and residence time remained stable.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies evaluated the charcoal and biochar qualities of some Costa Rican tropical woods, including energy densities, energy yields, biochar characteristics, and thermal profiles, in addition to other properties [20,[24][25][26], but when specifically studying the Costa Rican species in slow pyrolysis, Tectona grandis and Gmelina arborea lacked the same attention [27]; however, it does not refer to the effects of temperature in slow pyrolysis [28][29][30][31]. A study carried out on T. grandis by Parthasarathy and Sheeba [32] studied the yield, solid residence time, and charcoal characteristics produced at different temperatures of slow pyrolysis (300 • C, 350 • C, 450 • C, 500 • C, and 550 • C) and demonstrated that the yield of charcoal decreased, and residence time remained stable.…”
Section: Introductionmentioning
confidence: 99%